Peran Belanja Daerah dalam Meningkatkan Kesejahteraan dan Pembangunan Masyarakat - Anita Dewi Anggraini (Universitas Sains dan Teknologi Komputer, 2022)
economy in general as a progress that leads to an increase in the per capita income of the country, while at the same time improving the institutional system for example (economic, political, legal, social or cultural). National development has a goal, one of which is as an integral part of national development, therefore the need for appropriate regional economic growth so that the goals of national economic growth will be achieved. According to the term, economic development itself is involved in efforts such as increasing the standard of living in a country which is usually measured by the low level of per capita income. The purpose of this paper is to examine the correlation between regional spending on welfare and community development through a literature review, therefore it is important to understand and overcome problems in facing challenges to support community welfare and help achieve maximum economic development.